Analysis of Gender Differences in Determining Online Purchase Decision-Making Style on Fashion Products in Padang City - Yulmi Suari; Linda Wati; Surya Dharma (Management Institute Faculty of Economics Universitas Andalas, 2019)
Online shopping behavior refers to the process of purchasing products and services through the internet. Online Shopping is one of alternatives to purchase goods or services by men and women who are target market groups for marketers. Men and women tend to have different ways of thinking. The purpose of this study is to describe the differences between men and women, observed from their rationality in making decisions to purchase fashion products online. This study uses a decision-making style approach developed by Scott and Bruce (1995). In this study, the population is consumers living in the city of Padang who have purchased fashion products online at online shopping sites. There were 138 respondents who were sampled in this study. The sampling method uses accidental sampling. Data were analyzed using the Independent Sample T-test. This study found that there were differences in decision-making styles between men and women in purchasing fashion products online. In this case men are said to be more rational than women in making purchasing decisions online. Keywords: Online Shopping, Buyer Decision Making Style